Pendampingan Orang Tua dalam Pemanfaatan Teknologi oleh Anak di Rumah Studi Kasus di RA Miftahul Ulum 1 Jayasari - Ila Mustakimah; Nuri Andiani Putri; Parhatun Bidinillah; Wida Wargiati Solihah (Edu Happiness : Jurnal Ilmiah Perkembangan Anak Usia Dini, 2024)
This research aims to elaborate on how to assist parents in using technology by children in the case study home at RA Miftahul Ulum 1 Jayasari. This study uses a qualitative method. The respondents who joined this research were a number of parents who sent their children to the RA Miftahul Ulum 1 Jayasari education unit. The research results show that parents play an important role in assisting children in using technology. Parents can supervise their children and direct positive content for children that is appropriate to the child's growth and development.